The Impact of Russian Trade Sanctions on the Fertilizer Supply Chain in Indonesia - Rahmatika, Wa Ode Kodrat; Bainus, Arry; Yulianti, Dina (Intermestic: Journal of International Studies, 2025)
This research was conducted to analyze the impact of the Russian trade sanctions regime conflict on the Indonesian fertilizer supply chain using the concepts of inter-state conflict, international food trade and the global food system. As a result, researchers see the blockade of Ukrainian ports in 2022 as Russia's retaliatory action to restore the economic situation which has experienced a decline since 2014. The blockade is a driving factor in the food system, affecting the stability and availability of Indonesian fertilizer. Supply chain disruptions only resulted in a spike in fertilizer prices during the conflict, but did not significantly result in major losses for farmers. This analysis is based on the findings of Russian fertilizer import data which actually increased in 2022-2023 and the Indonesian government's quick response to the threat of decreasing fertilizer volumes and a spike in global fertilizer prices.